Inequity Aversion May Increase Inequity - Maria Montero (Fondazione Eni Enrico Mattei (FEEM), 2006)
Inequity aversion models have been used to explain equitable payoff divisions in bargaining games. I show that inequity aversion can actually increase the asymmetry of payoff division if unanimity is not required. This is due to the analogy between inequity aversion and risk aversion. Inequity aversion may also affect comparative statics: the advantage of being proposer can decrease as players become more impatient.
Keywords: A13; C78; 330; Noncooperative Bargaining; Coalition Formation; Inequity Aversion; Verhandlungstheorie; Koalition; Nichtkooperatives Spiel